Estrogen Deficiency Influences Hematological Parameters Following Bone Fracture in OVX Rats. (29th May 2020) - Munoz, Joseph; Juma, Shanil; Arjmandi, Bahram
Abstract: Objectives: Estrogen deficiency in postmenopausal women contributes to the development of osteoporosis. Furthermore, estrogen deficiency is associated with significant changes in hematological parameters including inflammatory markers. Since inflammation contributes to the pathophysiology of osteoporosis, the relationship between bone fracture, estrogen deficiency, and hematological parameters warrant investigation. Using an ovariectomized (OVX) rat model of postmenopausal osteoporosis, the objective of this research was to investigate the extent to which bone fracture in conditions of low estrogen affects hematological parameters compared to bone fracture in estrogen sufficient conditions. Methods: 12-month old Sprague Dawley rats were randomized into one of four groups (1. OVX + Fracture, 2. OVX + no fracture, 3. Sham + fracture, 4. Sham + no fracture). Rats randomized into the OVX + fracture and sham + fracture groups underwent fracture of the right fibula. After sacrificing the animals, blood was collected for analysis of hematological parameters. Results: All data are presented as mean ± S.E. As expected, OVX induced significant changes in hematological parameters compared to Sham. OVX compared to sham increased WBC (5.78 ± 0.93 vs. 1.73 ± 0.93 P < 0.01) and EOS (2.75 ± 0.39 vs. 1.50 ± 0.39 P < 0.05) and decreased PLT (357 ± 61 vs. 627 ± 61 P < 0.01). No changes were observed in hematological parameters of sham + fracture compared to sham. However, OVX + fracture increased MPV (6.33 ± 0.07 vs. 6.03 ± 0.09 P < 0.5) and tended to increase WBC (4.80 ± 0.66 vs. 2.73 ± 0.86 P = 0.06) and EOS (1.73 ± 0.28 vs. 0.81 ± 0.36 P = 0.55). Conclusions: These results are in accordance with previous reports indicating that OVX causes changes in hematological parameters. We also demonstrated that under conditions of bone fracture, OVX causes further changes in hematological parameters compared to sham. However, the implications in these changes for bone healing in conditions of low estrogen such as postmenopausal osteoporosis still need further investigation. Funding Sources: USDA.